33. NERVE BLOCK TREATMENT FOR CHRONIC GLOSSOPHARYNGEAL NEURALGIA: REPORT OF 2 CLINICAL CASES (Vietnam Journal of Community Medicine, 2024)
Objective: This article aims to report 02 rare cases of chronic glossopharyngeal neuralgia (9th nerve),treated by nerve block, thereby reviewing the literature.Case report: 02 patients were both misdiagnosed as 5th neuralgia on magnetic resonance imaging(MRI). However, the clinical symptoms are typical of 9th nerve pain. We used the 9th nerve blocktechnique for two patients, achieving good pain relief and no complications during and after theprocedure.Discussion: The discussion focuses on the definitive diagnosis, differential diagnosis and someminimally invasive interventional treatments of 9th neuralgia, emphasizing the effectiveness of theseinterventional methods.Conclusion: Chronic 9th neuralgia is a very rare disease that can be treated with nerve blocktechnique.
Keywords: 9th neuropathic pain, 5th neuropathic pain, nerve block.